Chlamydia trachomatis infections in infants. - Numazaki, K (1989)
In recent years considerable progress has been made in understanding chlamydial infections. The spectrum of pediatric Chlamydia trachomatis infection includes neonatal inclusion conjunctivitis, infantile pneumonia, occasional respiratory or genital tract infections in older children and sexually transmitted diseases in adolescents. The role of maternal chlamydial infection in prematurity and in perinatal death is currently an area of active study. We outline the current knowledge of the biologic characteristics of C. trachomatis, the epidemiologic features of chlamydial infection, and the clinical aspects, diagnosis and treatment of neonatal chlamydial infections.